Analisis Kinerja Bank Umum dengan menggunakan Metode Risk Based Bank Rating untuk Mengukur Kinerja Keuangan Bank dalam Struktur Modal sebagai Variabel Moderasi : Studi Kasus pada Bank BUMN yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2022 - Wilianti Wilianti; Sri Yuni; Septa Soraida (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2024)
The development of the banking industry in Indonesia is highly regarded, making the presence of banking institutions essential. It is known that the banking industry plays a strategic role in supporting the implementation of national development to enhance equitable development. To become a sufficiently good bank, measuring performance as an indicator of success is an absolute requirement. This research aims to determine whether the Risk Based Bank Rating approach can measure Financial Performance and the Risk Based Bank Rating moderated by Capital Structure can measure Financial Performance. Case study of state-owned banks listed on the Indonesia Stock Exchange in 2019-2022. This research uses secondary data and research methods used is quantitative. The results show that Non-Performing Loans have a negative impact on financial performance, the Loan to Deposit Ratio (LDR) has a significant impact on Return On Assets (ROA), the Net Interest Margin (NIM) has a positive and significant impact on financial performance measured by Return On Assets (ROA). Operating Expenses to Operating Income (BOPO) has a negative and significant impact on financial performance measured by Return On Assets (ROA). The Capital Adequacy Ratio (CAR) has a significant impact on financial performance. Capital Structure has a significant impact on Non-Performing Loans (NPL) compared to financial performance. Capital Structure significantly affects the Net Interest Margin (NIM) concerning financial performance. The capital structure between operating expenses and operating income can influence a company's performance.